胸膜巨大孤立性纤维瘤合并周围型肺动脉瘤1例 (Zhongguo Fei Ai Za Zhi, 2015)
Solitary fibrous tumor of pleura (SFTP) is uncommon, accounts for less than 5% of all pleural tumors. Pulmonary artery aneurysm (PAA) is also not common, 80% of which often occurs in the main pulmonary trunk and peripheral PAA is rare. SFTP combined with PAA in one patient has not been reported. This paper reports a case of SFTP combined with peripheral PAA, and SFTP maybe accelerate PAA formation.